2019
DOI: 10.31661/jbpe.v0i0.867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Volumetric Doses of Organs at Risk in Carcinoma Cervix Patients with HDR Intracavitary Brachytherapy and Comparison of CTbased and Conventional Plans

Abstract: Background: Brachytherapy treatment planning in cervix carcinoma patients using two dimensional (2D) orthogonal images provides only point dose estimates while CT-based planning provides volumetric dose assessment helping in understanding the correlation between morbidity and the dose to organs at risk (OARs) and treatment volume.Objective: Aim of present study is to compare International Commission on Radiation Units and Measurements Report 38 (ICRU 38) reference point doses to OARs with volumetric doses usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…3D CT and MRI are standardly used both for GTV coverage and evaluation of the dose to organs at risk (OARs), in particular for brachytherapy. Many authors had found correlations between late radiation toxicities and total dose given both to the rectum and bladder, as well as other studies had tried to give a possible comparison between late radiation toxicities and volumetric doses (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…3D CT and MRI are standardly used both for GTV coverage and evaluation of the dose to organs at risk (OARs), in particular for brachytherapy. Many authors had found correlations between late radiation toxicities and total dose given both to the rectum and bladder, as well as other studies had tried to give a possible comparison between late radiation toxicities and volumetric doses (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The ICRU recommends the use of rectal and bladder reference points for the dose assessment of normal organ tissues in HDR BT; however, with the continuous development of 3D BT technology, studies have confirmed that a DVH dose assessment based on CTV and OARs often differs from those based on ICRU reference points. DVH-based dose assessment results are more conformal and reliable, while TCP and NTCP calculations can be performed based on the results, which is conducive to individually designed radiotherapy plans and improved tumor control rates [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these points, the dose to two other points, which are 1.5 cm superior and inferior to the ICRU bladder points should also be recorded. In a study by Srivastava et al [45], it was observed that the dose at a point 1.5 cm above the ICRU bladder point was higher than the ICRU bladder point dose. This means that the ICRU bladder point is not the true representation of the maximum point dose to the bladder (Figure 7).…”
Section: Two-dimensional Image-based Brachytherapymentioning
confidence: 93%